EFL Students’ L2 Achievement: The Role of Teachers’ Organizational Commitment and Loving Pedagogy - Ye, Di; Sun, Suping; Zhao, Dongmei (Frontiers in Psychology, 2022)
Since student L2 achievement is the primary objective of all language education contexts, a huge number of inquiries have explored the role of students’ personal characteristics in promoting their L2 achievement. A plethora of studies have also assessed the impact of teachers’ personal and professional qualities on students’ L2 achievement. Yet, the effects of teachers’ organizational commitment and loving pedagogy have largely been neglected. In addition, no review article has been undertaken to outline the consequences of teachers’ organizational commitment and loving pedagogy for students’ L2 achievement. Against this backdrop, the present article intends to describe the role of teachers’ organizational commitment and loving pedagogy in EFL students’ L2 achievement by reviewing the theoretical and empirical evidence. The review revealed that teachers’ organizational commitment and loving pedagogy can favorably influence EFL students’ L2 achievement. The implications for language teachers, teacher trainers, and educational administrators are also discussed.